BER performance of M-ary pulse position modulated communication systems in anisotropic non-Kolmogorov turbulent atmosphere. Issue 2 (4th March 2022) - Ata, Yalçın; Baykal, Yahya; Gökçe, Muhsin Caner
Abstract : We investigated the effect of anisotropic non-Kolmogorov atmospheric turbulence on the performance of the optical wireless systems when M -ary Pulse Position Modulation (PPM) is applied to a Gaussian beam. The performance of the optical wireless systems that use avalanche photodetector at the receiver is evaluated in terms of the bit error rate (BER). The effects of the parameters, such as the anisotropy factors in x – y directions, modulation order, data bit rate, equivalent load resistor, photodetector quantum efficiency, non-Kolmogorov turbulence power law exponent, beam source size, link length, photodetector gain and structure constant on BER of the M -ary PPM Gaussian beam propagating in anisotropic non-Kolmogorov atmospheric turbulence, are examined.